Fil-dom-ed: As practiced in Letran Bataan - Mañez, James Emerson L. (Animo Repository, 2014)
"Love to study and study to love", these are the inspiring words of St. Dominic de Guzman. He is the founder of the Order of Preachers. Coming from these words of St. Dominic de Guzman, the Order of Preachers or the Dominicans led by Fr. Bruno Cadore, OP, Superior General of the order gave direct instruction to the Philippine Province to come up with a research project that would give light to the question. What is the Filipino Dominican Education and what is Filipino Dominican Philosophy pf Education? This paper is part of the said research project that would contribute a spark in giving light to the said question. It is a research project done in Colegio de San Juan de Letran, Abucay, Bataan using ethnography as its approach. This paper used the IMRaD format i.e., Introduction, Methodology, Results and Discussion. Using ethnography as its approach, the researcher had chosen a Theology class of his as student-participants of the said research. This ethnographical approach is in collaboration with other approaches of a research team, tasks to give light to the said question above.